2018
DOI: 10.15587/2519-8025.2018.128653
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity of azithromycin against Staphylococcus epidermidis

Abstract: Метою дослідження було встановлення специфічної активності азитроміцину відносно біоплівки, сформованої S. epidermidis та деяких аспектів механізму дії препарату. Здатність стафілококу до адгезії на абіотичній поверхні (полістиролові планшети) визначали за методикою Christensen (фіксація 96 % етанолом, фарбування 0,1 % р-ном генціанвіолету). Антибіоплівкову активність азитроміцину досліджували методом сорбції генціанвіолету на структурах біоплівки з подальшою десорбцією в 96 % етиловий спирт. Гідрофобність шта… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Previously, we had found that 1-[4-(1,1,3,3-tetra methyl butyl) phenoxy]-3-(N-benzyl hexa methylene iminium)-2-propanol chloride (KVM-194) showed a broad spectrum of antibacterial activity (13), among which -in vitro activity against biofilms of gram-negative and gram-positive bacteria (14,15,16). As KVM-194 possessed membranotropic effects and affected the composition of cell walls of gram-negative bacteria (17), we hypothesized that this compound could affect bacterial cell surface properties and adhesion to polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we had found that 1-[4-(1,1,3,3-tetra methyl butyl) phenoxy]-3-(N-benzyl hexa methylene iminium)-2-propanol chloride (KVM-194) showed a broad spectrum of antibacterial activity (13), among which -in vitro activity against biofilms of gram-negative and gram-positive bacteria (14,15,16). As KVM-194 possessed membranotropic effects and affected the composition of cell walls of gram-negative bacteria (17), we hypothesized that this compound could affect bacterial cell surface properties and adhesion to polystyrene.…”
Section: Introductionmentioning
confidence: 99%